Electrosynthesis of Au nanocluster embedded conductive polymer films at soft interfaces using dithiafulvenyl-functionalized pyrene. Issue 12 (2nd March 2023) - Moshrefi, Reza; Ryan, Katelyn; Connors, Evan P.; Walsh, Joshua C.; Merschrod, Erika; Bodwell, Graham J.; Stockmann, Talia Jane
Abstract : Ultra-thin Au nanoparticle (NP) embedded conductive polymer films have been electrosynthesized at a micro-ITIES. Abstract : Nanoparticle (NP) embedded conductive polymer films are desirable platforms for electrocatalysis as well as biomedical and analytical applications. Increased catalytic and analytical performance is accompanied by concomitant decreases in NP size. Herein, highly reproducible electrogeneration of low dispersity Au nanocluster embedded ultra-thin (∼2 nm) conductive polymer films at a micro liquid|liquid interface is demonstrated. Confinement at a micropipette tip facilitates a heterogeneous electron transfer process across the interface between two immiscible electrolyte solutions (ITIES), between KAuCl4 (aq) and a dithiafulvenyl-substituted pyrene monomer, 4, 5-didecoxy-1, 8-bis(dithiafulven-6-yl)pyrene (bis(DTF)pyrene), in oil, i.e., a w|o interface. At a large ITIES the reaction is spontaneous, rapid, and proceeds via transfer of AuCl4 − to the oil phase, followed by homogeneous electron transfer generating uncontrolled polymer growth with larger (∼50 nm) Au nanoparticles (NPs). Thus, miniaturization facilitates external, potential control and limits the reaction pathway. Atomic (AFM) and Kelvin probe force microscopies (KPFM) imaged the topography and work function distribution of the as-prepared films. The latter was linked to nanocluster distribution.